ANALISIS PENGEMBANGAN KELAPA SAWIT DI KALIMANTAN - Munawir Munawir; Sukiman Sukiman; Akka Latifah Jusdienar; Joko Budiraharjo; Andy Sukrisno; Muhammad Yahdi (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
This study aims to determine the extent of the development / development of oil palm in Kalimantan, in terms of the area, production, productivity of palm oil and labor absorption and its contribution to the scale of Indonesia. Here, Kalimantan ranks second after Sumatra. Kalimantan's contribution to Indonesia for the last 3 years until 2023, the area ranges from 34.79% to 39.49% (5,856,853 ha to 6,038,573 ha), production ranges from 38.62% to 42.44% (17,587,623 tons to 20,472,160 tons), productivity is 3,604 tons / ha to 4,192 tons / ha, the number of farmers ranges from 478,720 families to 516,146 families and the number of workers ranges from 2,273,901 kindergartens to 2,343,031 kindergartens, The distribution of oil palm is in West Kalimantan (13 districts), Central Kalimantan (14 districts), South Kalimantan (13 districts), East Kalimantan (10 districts), and North Kalimantan (5 districts).